Advances in Room Temperature of Indium Aluminum Nitride InAlN Deposition via Direct Current (DC) Co-Sputtering for Solar Energy Applications - Juan David Cañón-Bermúdez; Luis Fernando Mulcué-Nieto (Energies)
This study presents an innovative method for the synthesis of indium aluminum nitride (InAlN) layers by direct current (DC) co-sputtering at room temperature, with the aim of reducing production costs of optoelectronic devices. Indium and aluminum targets are used, varying the power applied to the aluminum target. The results show that increasing the target power favors the formation of aluminum nitride (AlN), which modifies the chemical composition of the material. The layers obtained present smooth surfaces with a roughness of less than 3 nm, which is beneficial for applications requiring interfaces with low defect density. Regarding the optical properties, it is observed that the optical bandgap varies between 1.8 eV and 2.0 eV, increasing with the target power. Hall effect measurements indicate a decrease in the free carrier concentration and an increase in the resistivity with increasing power. This approach allows for the synthesis of InAlN with properties suitable for optoelectronic applications, solar cells, photocatalysis, and photoelectrocatalysis at low cost.